2015
DOI: 10.1002/bies.201500031
|View full text |Cite
|
Sign up to set email alerts
|

Keeping it together: Pulmonary alveoli are maintained by a hierarchy of cellular programs

Abstract: The application of in vivo genetic lineage tracing has advanced our understanding of cellular mechanisms for tissue renewal in organs with slow turnover, like the lung. These studies have identified an adult stem cell with very different properties than classically understood ones that maintain continuously cycling tissues like the intestine. A portrait has emerged of an ensemble of cellular programs that replenish the cells that line the gas exchange (alveolar) surface, enabling a response tailored to the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…Our findings show that TNRC6c plays an essential role in airway sacculation that is upstream of TGFβ, and suggest that it normally acts indirectly by effecting degradation of one or more mRNAs that encode an inhibitor of TGFβ1 and TGFβR2 expression. Identifying these putative mRNAs will be a high priority, since they could be involved in the pathogenesis of neonatal lung diseases in which both alveolar mesenchyme and microvasculature is disrupted, like bronchopulmonary dysplasia, or be harnessed for promoting repair of the gas exchange interface following injury in adult life (Logan and Desai, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that TNRC6c plays an essential role in airway sacculation that is upstream of TGFβ, and suggest that it normally acts indirectly by effecting degradation of one or more mRNAs that encode an inhibitor of TGFβ1 and TGFβR2 expression. Identifying these putative mRNAs will be a high priority, since they could be involved in the pathogenesis of neonatal lung diseases in which both alveolar mesenchyme and microvasculature is disrupted, like bronchopulmonary dysplasia, or be harnessed for promoting repair of the gas exchange interface following injury in adult life (Logan and Desai, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Unlike the cells of origin for two other major lung cancer subtypes, adenocarcinoma (alveolar type 2 cells 7 ) and squamous cell carcinoma (presumed to be tracheo-bronchiolar basal cells 8 ), a rare sensory cell type termed pulmonary neuroendocrine cells are the predominant cell of origin for SCLC 9 . Dr. Krasnow’s laboratory has demonstrated that the transformation processes for each of these cell types are similar in that characteristic oncogenes such as EGFR, KRAS , etc.…”
Section: Etiology and Cell Of Origin Of Sclc And Related Neuroendocrimentioning
confidence: 99%
“…Genetic studies in mice support a hierarchy of adult stem cells that can replenish the alveolar gas exchange surface (11), some of which are active only following massive injury (1214). Under normal homeostatic conditions, the alveolar epithelium is maintained by rare ‘bifunctional’ alveolar epithelial type 2 (AT2) cells, cuboidal cells that retain the surfactant biosynthesis and secretory function of standard ("bulk") AT2 cells (15) but also serve as stem cells that renew the alveolar epithelium throughout the lifespan (16, 17).…”
Section: Introductionmentioning
confidence: 99%